2013
DOI: 10.1016/j.jcf.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis CFBE41o‐ cells contain TLR1 SNP I602S and fail to respond to Mycobacterium abscessus

Abstract: Background Mycobacterium abscessus causes lung infection in patients with cystic fibrosis. M. abscessus stimulates the host innate immune response via TLR2 on respiratory epithelial cells. Signaling through TLR2 requires the formation of TLR2/TLR1 heterodimers on the cell surface. Methods The ability of M. abscessus to stimulate the innate immune response of cystic fibrosis CFBE41o- respiratory epithelial cells was measured as expression of HβD2 by RT PCR, and release of IL-8 by ELISA. Genotyping of CFBE41o-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…an anaerobic gram-negative bacterium belonging to the respiratory tract microbiota (43). In the case of M. abscessus , previous works demonstrated that bronchial epithelial cells generate a hyporesponsive response since M. abscessus S fail to elicit a Toll-like receptor 2 (TLR2) response and only a precise cell fraction from R morphotype exhibits TLR2 stimulating activity (44), which is necessary for the activation of the signaling cascade that triggers the secretion of the cytokines IL-6 and IL-8 (45). This lack of immune response activation observed is particularly high in the case of the S morphotype (as supported by our results) since the presence of GPL in its cell wall masks other molecules that would activate TLR2 signaling (46).…”
Section: Discussionmentioning
confidence: 99%
“…an anaerobic gram-negative bacterium belonging to the respiratory tract microbiota (43). In the case of M. abscessus , previous works demonstrated that bronchial epithelial cells generate a hyporesponsive response since M. abscessus S fail to elicit a Toll-like receptor 2 (TLR2) response and only a precise cell fraction from R morphotype exhibits TLR2 stimulating activity (44), which is necessary for the activation of the signaling cascade that triggers the secretion of the cytokines IL-6 and IL-8 (45). This lack of immune response activation observed is particularly high in the case of the S morphotype (as supported by our results) since the presence of GPL in its cell wall masks other molecules that would activate TLR2 signaling (46).…”
Section: Discussionmentioning
confidence: 99%
“…The Mabs 390R rough strain used in this study has been previously described (5,(15)(16)(17)(18)(19). It has been determined to be Mycobacterium abscessus subspecies abscessus (UT Health, The University of Texas Health Sciences Center at Tyler, Barbara A. Brown-Eliot).…”
Section: Bacteria and Lung Infectionmentioning
confidence: 99%
“…This cell line is hyporesponsive to TLR2/TLR1 receptor agonist and the rough MABS 390R strain. This SNP is likely to be present in the CF patient population ( Kempaiah et al, 2013 ). Paradoxically the presence of this SNP is protective against infection with Mycobacterium leprae ( Johnson et al, 2007 ).…”
Section: The Paradox Of Low Virulence and Ineffective Host Responsementioning
confidence: 99%